Explanation of Some Electrochemical Phenomena with the Theory of Disproportionation of Atom— 3 : Effect of Anions on the Corrosion of Aluminium in Sodium Hydroxide Solution - Awad, A.; Kassab, A.A.; Misbah, A.A.; Abd El-Wahhab, E. (Asian Journal of Chemistry, 2010)
In the present work the effect of anions on the corrosion of aluminium in sodium hydroxide solutions has been described.